EVOLUTION OF MARKETING CONCEPTS: FROM CLASSIC EXCHANGE TO CONSUMER EXPERIENCE - YANOVSKA, Viktoriia; PYLYPENKO, Olena; TVORONOVICH, Viktoriia; USTILOVSKA, Anastasiia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article presents a comprehensive analysis of the evolution of marketing concepts and models from the classical transactional logic of exchange to modern relational, digital and experiential approaches. A systematic analysis of the key characteristics of each concept is carried out, their advantages and limitations are identified, and how they affect the effectiveness of interaction with the consumer and long-term customer value is shown. Special attention is paid to the integration of behavioral, cognitive and technological aspects in relational and digital marketing, as well as the use of modern analytics tools, CRM systems, data management platforms and artificial intelligence technologies to personalize communications, optimize marketing decisions, and enhance consumer engagement.The article outlines the historical stages of the development of marketing concepts, reflecting the shift from transactional to relational, digital and experiential marketing, demonstrating how paradigm shifts in marketing thinking are embodied in business strategies, forms of communication, management priorities and the use of technology to form a value-oriented and human-centric approach. Modern digital marketing models are considered, in particular the 5E and 7E approaches, which emphasize the life cycle of consumer experience and multidimensional interaction with the brand in physical, digital and mixed environments. These models enable companies to respond more flexibly to consumer needs by creating an integrated, personalized, and emotionally resonant experience. The findings allow for a systematic understanding of contemporary trends in marketing thought and practice, emphasizing the importance of integrating analytical, digital, and behavioral approaches into marketing activities. The study provides practical guidance for improving business process efficiency. It demonstrates that marketing transformation is a continuous process in which paradigm shifts reflect adaptation to a dynamic environment, technological advancements, and changes in consumer behavior. This transformation enables organizations to generate long-term value and strategic advantage within the modern digital and networked economy.
Keywords: marketing; marketing concepts; marketing evolution; transactional marketing; relational marketing; digital marketing; experiential marketing; value co-creation; consumer experience